2018
DOI: 10.1155/2018/5406467
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Colonization by Moraxella catarrhalis and Tonsillar Hypertrophy

Abstract: We sought to investigate the prevalence of potentially pathogenic bacteria in secretions and tonsillar tissues of children with chronic adenotonsillitis hypertrophy compared to controls. Prospective case-control study comparing patients between 2 and 12 years old who underwent adenotonsillectomy due to chronic adenotonsillar hypertrophy to children without disease. We compared detection of Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Pseudomonas aeruginosa, and Moraxella catarrhalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
1
9
1
3
Order By: Relevance
“…Other studies have also identified that patients with OSA or TH have a higher relative abundance of Haemophilus ( 7 ) and Streptococcus ( 12 ) than RT patients. Moreover, the main species of Moraxella ( 13 ) and Neisseria ( 9 ) have also proven to be positively correlated with the occurrence of TH in previous research. Dialister ( 14 ), Aggregatibacter ( 15 ), and Atopobium ( 16 ), which were present significantly more in CT patients, have been demonstrated to be increased in several infective and inflammation-related diseases, including acute tonsillitis ( 16 ).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Other studies have also identified that patients with OSA or TH have a higher relative abundance of Haemophilus ( 7 ) and Streptococcus ( 12 ) than RT patients. Moreover, the main species of Moraxella ( 13 ) and Neisseria ( 9 ) have also proven to be positively correlated with the occurrence of TH in previous research. Dialister ( 14 ), Aggregatibacter ( 15 ), and Atopobium ( 16 ), which were present significantly more in CT patients, have been demonstrated to be increased in several infective and inflammation-related diseases, including acute tonsillitis ( 16 ).…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the main species of Moraxella (13) and Neisseria (9) have also proven to be positively correlated with the occurrence of TH in previous research. Dialister (14), Aggregatibacter (15), and Atopobium (16), which were present significantly more in CT patients, have been demonstrated to be increased in several infective and inflammation-related diseases, including acute tonsillitis (16). Notably, Haemophilus and Neisseria, which have higher abundance in tonsillar microbiota type 3, were significantly increased in the TH patients, highlighting the potential role of these bacteria in the occurrence of TH (8,9).…”
Section: Discussionmentioning
confidence: 93%
“…Another point to consider about the bacterium M. catarrhalis is that its prevalence has rarely been evaluated by precise and sensitive molecular methods including PCR, real-time PCR, and loop-mediated isothermal amplification in ocular infections; while most studies of the presence of this bacterium in the respiratory specimens were done with molecular assessment in parallel with the conventional culture method [ 3 , 23 ]. This may indicate that the actual prevalence of this bacterium in ocular infections is lower than the original rate, as the use of molecular methods is much more specific and sensitive than the conventional culture method.…”
Section: Discussionmentioning
confidence: 99%
“…Moraxella cataralis в нёбных миндалинах с их более выраженной гипертрофией [13]. Имеются исследования, результаты которых свидетельствуют о связи ГНМ с наличием биопленок микроорганизмов в их криптах [14].…”
Section: ____________________________________________________________...unclassified